The significance of political leaders for social policy expansion in Brazil, China, India and South Africa. Issue 3 (3rd July 2017) - Manor, James; Duckett, Jane
ABSTRACT: This paper examines the roles that political leaders have played in the formulation and implementation of government initiatives to tackle poverty and inequality in Brazil, China, India and South Africa since about 2002. While research on social policy and welfare expansion in the industrialised world has largely ignored leaders, we stress the importance of politics and political agency, since political leaders often exercised decisive influence even if their decisions to prioritise certain issues and to adopt certain strategies depend on the convergence of other factors. We examine their management of tensions and opposition within their governments and their political systems – as well as what we can discern of their motivations and political calculations. We consider the impact on government initiatives both of their adroit machinations and, at times, of their ineptitude.